Cover Feature: SnO2 Based Catalysts with Low‐Temperature Performance for Oxidative Coupling of Methane: Insight into the Promotional Effects of Alkali‐Metal Oxides (Eur. J. Inorg. Chem. 17/2018). Issue 17 (14th April 2018) - Peng, Liang; Xu, Junwei; Fang, Xiuzhong; Liu, Wenming; Xu, Xianglan; Liu, Liang; Li, Zhongchen; Peng, Honggen; Zheng, Renyang; Wang, Xiang
Abstract : The Cover Feature shows how the addition of a suitable amount of lithium oxide into SnO2 can remarkably improve its performance in the oxidative coupling of methane, especially in the low‐temperature region below 750°C. Both the surface electrophilic oxygen species and the alkaline sites with intermediate strength are critical for the target reaction. For a catalyst with a Sn/Li molar ratio of 5:5, equal amounts of SnO2 ) and Li2 SnO3 crystalline phases are formed in the bulk, which results in the largest amounts of both surface‐active sites and leads to the best catalytic performance. More information can be found in theFull Paper by X. Wang et al.